Nutritional and ruminal degradability of oil palm fronds improvement using enzyme extract from filamentous fungi - Azmi, Mohammad Azri (2020)
In Malaysia, ruminant production still struggles to fulfill the local demands for human consumption. It is due to high cost which feeding cost constitute to 70% of the total production cost. The industry relies on locally available feed resources such as crop residues and agricultural by-products, apart from supplementation with concentrates made up from mainly imported ingredients. Malaysia is one of the most prominent producers of palm oil and produces approximately 30 million tonnes of oil palm fronds annually as agricultural by-product. However, its effective utilization is hindered by its high lignin content and low protein content. The presence of the lignin creates a barrier which prevent the access of rumen microbe toward the fermentable substrate. Several methods have been explored in removing the lignin content of the agricultural by-product. Biological pretreatment presents as viable option in enhancing the usage of agricultural by-product. Fungi is the best organism to degrade lignin due to its ability to produce lignolytic enzymes. In Objective 1, 11 fungi were isolated from rotten oil palm fronds. Their enzymes activity was determined. In Objective 2, based on enzymes activity in Objective 1, F1, F2 and F4 showed the most conducive enzyme activity profile compared to other fungi. The isolated F1, F2 and F4 identified as Trichoderma harzianum MK027305, Trichoderma harzianum MK027306, and Fusarium solani MK027309, respectively. In Objective 3, the oil palm fronds were pretreated with the enzymes extract extracted from the selected fungi. The enzyme extracts were obtained using 15, 30 and 45 days of solid-state fermentation. The oil palm fronds were then subjected to pretreatment using the enzyme extracts and tested for its in vitro ruminal degradability. From the study, it is found that the oil palm fronds pretreated with enzyme extract from the fungi Trichoderma harzianum MK027305 at 15 days of solid-state fermentation produces the highest total gas production at 13.5 mL of gas produced while highest methane production was observed on oil palm fronds pretreated with enzymes extract from Trichoderma harzianum MK027306 at 30 days of solid-state fermentation at 8.25 mL. The highest fatty acid production was exhibited by oil palm fronds pretreated by Fusarium solani MK027309 at 45 days of fermentation at 58.151 mmol/dl for acetic acid, 22.747 mmol/dl for propionic acid and 65.093 mmol/dl for butyric acid. The pretreatment of oil palm fronds with enzyme extract from Fusarium solani MK027309 at 45 days of solid-state fermentation showed an increase of 21.67% total volatile fatty acid produced as compared to diet with untreated OPF with increase of 35.29% of apparent rumen degradable carbohydrate for g/g of OPF. In conclusion, the pretreatment using enzyme extract from Fusarium solani MK027309 after 45 days of fermentation via solid state fermentation showed successful result in increasing the ruminal degradability of oil palm fronds by 35.29%.